Experimental investigation and parametric optimization in abrasive jet machining on nickel 233 alloy using WASPAS and MOORA. Issue 1 (1st January 2018) - Prasad, S. Rajendra; Ravindranath, K.; Devakumar, M. L. S.
Abstract: This article correspond to a multi criterion decision making approach, compared with Multi-Objective Optimization on the Weighted Aggregated Sum Product Assessment (WASPAS) and ratio analysis (MOORA) to optimize different interconnected responses during Abrasive jet machining (AJM) process of Nickel 233 alloy. The response parameters preferred are the average material removal rate (MRR) surface roughness (Ra) and Taper angle (Ta). The entire of them have been calculated in terms of injecting pressure, standoff distance, and abrasive grain size. The proposed technique Weighted Aggregated Product Sum Assessment technique is investigation of parametric optimization on AJM process. The outcome acquired using the WASPAS method demonstrate perfect parallel with those obtained by the ratio analysis (MOORA) method which confirms the applicability and potentiality of these MCDM methods for resolving compound AJM process parameter selection problems.